2017
DOI: 10.1002/app.46071
|View full text |Cite
|
Sign up to set email alerts
|

Comparative mucoadhesive study of hyaluronic acid‐based conjugates on different mucosae

Abstract: The incentive of this study was to provide a detailed mucoadhesive comparison on adhesive properties on diverse mucosal surfaces such as nasal, buccal, and vaginal mucosa, respectively. Mucoadhesive hyaluronic acid-cysteine ethyl ester (HA-SH) conjugate was synthesized by the anchorage of sulfhydryl groups (SH) on the polymeric backbone of HA via amide bond formation between the carboxylic acid moieties of hyaluronic acid and sulfhydryl groups of cysteine ethyl ester. Histology assay in terms of alcian blue st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Non-PEGylated HA-LX were able to diffuse through mucus, although HA is normally used as a biopolymer for mucoadhesive systems implicated on the entanglement of polymeric chains with mucin fibers. 45,46 In the present work the presence of HA increase LX diffusion in the ±4:1 charge ratio. In vitro and in vivo studies showed that the HA coating on a nanocomplexation formed insulin/L-penetrating nanoparticles enhanced mucopenetrating ability through intestinal mucus layer after oral administration.…”
Section: Resultssupporting
confidence: 51%
“…Non-PEGylated HA-LX were able to diffuse through mucus, although HA is normally used as a biopolymer for mucoadhesive systems implicated on the entanglement of polymeric chains with mucin fibers. 45,46 In the present work the presence of HA increase LX diffusion in the ±4:1 charge ratio. In vitro and in vivo studies showed that the HA coating on a nanocomplexation formed insulin/L-penetrating nanoparticles enhanced mucopenetrating ability through intestinal mucus layer after oral administration.…”
Section: Resultssupporting
confidence: 51%
“…The same conclusion was obtained with the pig eye, both normal peak force and area under force-time curve were higher with HA 0.30% than with HA 0.15%. Tensile strength assay on nasal, buccal and vaginal mucosa performed by Laffleur [34] using HA-based conjugates also showed similar adhesive bonding force between HA and the different mucosas, ranging between −0.1 and −0.2 N. According to Hägerström and Edsman, who performed a similar assay, the strengthening might arise from the entanglement of the polymer chains and the mucous glycoproteins, the formation of chemical bonds and/or from dehydration of the mucous layer [13]. However, the area under force-time curve values did not meet the same profile as the normal force, there were no significant difference between HA 0.15% vs. Mucin + HA 0.15% and HA 0.30% vs. Mucin + HA 0.30%.…”
Section: Discussionmentioning
confidence: 99%
“…131 Similarly, hyaluronic acid (HA) functionalized with sulfhydryl cysteine groups (HA-SH) significantly outperformed unmodified HA in terms of tensile strength, total work of adhesion, and maximum detachment force in nasal, buccal, and vaginal tissue. 132 To increase the mucoadhesive capacity of chitosan, Kim et al utilized a mussel-inspired adhesion approach and synthesized catechol-functionalized chitosan (Chi-C). 133 As shown in Figure 3, catechols can oxidize to form irreversible covalent bonds with thiols and amines within mucus, leading to greater bioavailability and retention time of Chi-C in the GI tract following oral administration.…”
Section: Mucoadhesion Mucoadhesion Has Been Widelymentioning
confidence: 99%
“…SH-modified alginate possessed a ∼4-fold higher work of adhesion when applied on freshly excised mucosa as compared to unmodified alginate . Similarly, hyaluronic acid (HA) functionalized with sulfhydryl cysteine groups (HA-SH) significantly outperformed unmodified HA in terms of tensile strength, total work of adhesion, and maximum detachment force in nasal, buccal, and vaginal tissue . To increase the mucoadhesive capacity of chitosan, Kim et al utilized a mussel-inspired adhesion approach and synthesized catechol-functionalized chitosan (Chi-C) .…”
Section: Formulation Strategiesmentioning
confidence: 99%